The Effectiveness of Stress Management and Resilience Training (SMART) on Psychological Well-Being in Patients with Thalassemia Major - Mohammad Reza Babaei; Gasem Askarizadeh; Afsaneh Towhidi (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Thalassemia is one of the main chronic hereditary diseases characterized by severe symptoms of anemia. Also, it has negative effects on patients' mental health. However, few researches have studied the different psychiatric aspects of this disease and the psychological and social needs of thalassemic patients. Objectives: The aim of the present study was to investigate the effect of stress management and resilience training on psychological well-being of thalassemic patients in Kerman. Methods: This research was a quasi-experimental study using pre-test and post-test model with control group. A sample of 30 patients with thalassemia major, who referred to the Samen al-Hojaj Charity Foundation, was selected through convenience sampling and randomly divided into experimental and control groups (each group included 15 patients). After completing the pre-test, the experimental group received 10 sessions of stress management training. The instrument of the study was Reef Psychological Well-being Questionnaire (RPWB). Data were analyzed by SPSS software using covariance analysis. Results: The results indicated that resilience and stress management training have positive effects on psychological well-being and its subscales including self-acceptance, positive relationship with others, autonomy, personal development and purposeful life of thalassemia major patients (p<0.05), yet it is not effective on environmental control (p>0.05). Conclusion: According to the results, regarding the effectiveness of resilience and stress management on the psychological well-being of thalassemic patients, the present study could introduce effective solution for development of psychological well-being and improvement of overall mental health of patients with thalassemia major